DYNAMIC CHANGES OF TRAb AND TPOAb AFTER RADIOIODINE THERAPY IN GRAVES’ DISEASE - Dong, Q. (Acta Endocrinol (Buchar), 2017)
CONTEXT: To analyze the dynamic changes of serum thyrotrophin receptor antibody (TRAb) and thyroid peroxidase antibody (TPOAb) in Graves’ disease (GD) patients before and after radioactive iodine (RAI) treatment and to investigate if TRAb and TPOAb play a role in the occurrence of early hypothyroidism after (131)I therapy for Graves’ hyperthyroidism. SUBJECTS AND METHODS: A total of 240 patients newly diagnosed with GD were selected to study. A clinical and laboratory assessment was performed before and at 3, 6, and 12 months after (131)I therapy. Chemiluminescent immunoassays were used to detect serum free triiodothyronine (FT3), free thyroxine (FT4), sensitive thyroid-stimulating hormone (TSH) and TPOAb concentration. Radio-receptor assay was used to measure serum TRAb concentration. According to the early onset of hypothyroidism in a year after RAI therapy, patients were divided into early hypothyroidism group (group A) and non-early hypothyroidism group (group B). RESULTS: In both groups, serum TRAb and TPOAb increased at 3 months, reached the highest level at 6 months and returned to the baseline at 12 months after RAI therapy. TRAb showed a significant difference between the two groups at 6 months (P<0.01). Serum TPOAb in group A was higher than that in group B before and at 3, 6, 12 months after RAI therapy (P<0.05). CONCLUSIONS: Serum TRAb and TPOAb are closely related to the occurrence of the early hypothyroidism, and play an important role in judging prognosis after (131)I treatment in Graves’ disease.